Association between Single Nucleotide Polymorphisms rs3757318 and Vitamin D Deficiency in Iraqi Breast Cancer Patients - Istikrar M. Hade; Ahmed S. K. Al-Khafaji; Fadhel M. Lafta; Yasir B. Qaddoori (Medical Journal of Babylon)
Background: Multiple single-nucleotide polymorphisms (SNPs) located in the intergenic region between estrogen receptor 1 and CCDC170 (especially at rs3757318) are thought to be associated with breast cancer risk. additionally, the serum level of vitamin D is believed to be linked to different aspects of breast carcinogenesis. Objectives: To assess the potential association between rs3757318 SNP and breast cancer pathogenicity, specifically in relation to serum vitamin D levels. Materials and Methods: For addressing this issue, 100 subjects were enrolled in this work, including 50 female patients diagnosed with breast cancer recruited from the Oncology Hospital, Baghdad, Iraq and 50 apparently healthy women with no malignancies as a control group. The serums level of vitamin D was measured for breast cancer patients and healthy controls groups, whereas, CCDC170 rs3757318 SNP genotypes were assessed using TaqMan SNP genotyping and utilizing genomic DNA extracted from the participants. Results: Vitamin D levels were shown to be significantly reduced (P < 0.001) in breast cancer patients than that of the healthy controls (6.604 vs. 22.268, respectively). In respect to the CCDC170 gene rs3757318 SNP genotypes frequency, the mutant genotype (AA) was only identified in the investigated breast cancer patients (O.R. (C.I.) = 1.69 (0.86–2.07)) and this seems to confer the increased risk of breast cancer susceptibility. Conclusion: Overall, the findings of the present study suggest an association between the reduced vitamin D levels and CCDC170 gene rs3757318 SNP genotypes frequency in breast carcinogenesis.